Origin of the early Cenozoic belt boundary thrust and Izanagi–Pacific ridge subduction in the western Pacific margin - Kimura, Gaku (2019)
The belt boundary thrust within the Cretaceous–Neogene accretionary complex of the Shimanto Belt, southwestern Japan, extends for more than ~ 1 000 km along the Japanese islands. A common understanding of the origin of the thrust is that it is an out of sequence thrust as a result of continuous accretion since the late Cretaceous and there is a kinematic reason for its maintaining a critically tapered wedge. The timing of the accretion gap and thrusting, however, coincides with the collision of the Paleocene–early Eocene Izanagi–Pacific spreading ridges with the trench along the western Pacific margin, which has been recently re‐hypothesized as younger than the previous assumption with respect to the Kula‐Pacific ridge subduction during the late Cretaceous. The ridge subduction hypothesis provides a consistent explanation for the cessation of magmatic activity along the continental margin and the presence of an unconformity in the forearc basin. This is not only the case in southwestern Japan, but also along the more northern Asian margin in Hokkaido, Sakhalin, and Sikhote‐Alin. This Paleocene–early Eocene ridge subduction hypothesis is also consistent with recently acquired tomographic images beneath the Asian continent. The timing of the Izanagi–Pacific ridge subduction along the western Pacific margin allows for a revision of the classic hypothesis of a great reorganization of the Pacific Plate motion between ~ 47 Ma and 42 Ma, illustrated by the bend in the Hawaii–Emperor chain, because of the change in subduction torque balance and the Oligocene–Miocene back arc spreading after the ridge subduction in the western Pacific margin.